2020
DOI: 10.1016/j.metop.2020.100024
|View full text |Cite
|
Sign up to set email alerts
|

The alpha-glucosidase inhibitor miglitol increases hepatic CYP7A1 activity in association with altered short-chain fatty acid production in the gut of obese diabetic mice

Abstract: Purpose Bile acids (BAs) have been shown to contribute to glucose and energy homeostasis. We have recently reported that miglitol, an alpha-glucosidase inhibitor, increases fecal BA excretion and ameliorate insulin resistance and obesity in mice. The aim of this study was to clarify the mechanisms by which miglitol affects BA metabolism. The expression of genes regulating BA metabolism, gut microbiome and short-chain fatty acids (SCFA) were examined. Procedures NSY mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…It is involved in the mechanism of reducing liver steatosis and blood lipids. 51 Some studies have found that the content of secondary bile acids in the hypothalamus of obese mice is significantly reduced. When a TGR5 agonist is given, the sympathetic nervous system is activated, which can reduce obesity and promote energy balance; 52 TGR5 is involved in the inhibition of dietary secondary bile acids in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in the mechanism of reducing liver steatosis and blood lipids. 51 Some studies have found that the content of secondary bile acids in the hypothalamus of obese mice is significantly reduced. When a TGR5 agonist is given, the sympathetic nervous system is activated, which can reduce obesity and promote energy balance; 52 TGR5 is involved in the inhibition of dietary secondary bile acids in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have discovered that increased SCFAs induce the upregulation of cytochrome p-450 enzyme cholesterol 7α-hydroxylase (CYP7A1) ( 70 ) and 27α-hydroxylase (CYP27A1) ( 71 ) in the liver. Upregulation of CYP7A1 promotes cholesterol converted into BAs ( 72 ), thereby increasing cholesterol consumption and lowering LDL-C levels.…”
Section: Points Of Contact Between Gut Microbiota and Cholesterol Met...mentioning
confidence: 99%
“…Existing studies have found that proteins that regulate lipid and glucose metabolism are significantly inhibited under diabetic settings, such as glucose transporter 2 (GLUT2), cholesterol 7 alpha-hydroxylase (CYP7A1), G-protein-coupled bile receptor (TGR5), and Farnesyl X receptor (FXR) [20,21]. To study the mechanism of TFA on bile acid metabolism, their protein expression was determined by western blot.…”
Section: Tfa Improved Glucose and Lipid Metabolism In The Liver Of Diabetic Micementioning
confidence: 99%